(untitled) (El Taco en la Brea, 2025)
This article examines the autobiographical writings of contemporary exiled writers in France and Germany, focusing on their experience of displacement and the identity contradictions they face. It explores how the conditions of forced migration, such as social precariousness and language acquisition, mark a rupture in the lives of exiles and engender a sense of social decline. It also addresses factors like gender, sexual identity, origins and reasons for exile to understand the variations in their narratives from a sociological perspective. We draw on analytical tools developed in the study of «class defectors» to examine how exile narratives can be read both as accounts of social downgrading and mobility, but also in their specificity: produced within configurations of social marginalization, shaped by the expression of precarization and, in some cases, by traumatic experiences linked to exile. The writers reinvent their identity and storytelling in the context of exile, contributing to the transformation of contemporary narrative forms.